2006
DOI: 10.1152/ajpheart.01180.2005
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac microimpedance measurement in two-dimensional models using multisite interstitial stimulation

Abstract: . Cardiac microimpedance measurement in two-dimensional models using multisite interstitial stimulation. Am J Physiol Heart Circ Physiol 290: H1976 -H1987, 2006. First published December 22, 2005 doi:10.1152/ajpheart.01180.2005.-We analyzed central interstitial potential differences during multisite stimulation to assess the feasibility of using those recordings to measure cardiac microimpedances in multidimensional preparations. Because interstitial current injected and removed using electrodes with differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…7,8,33,34 Importantly, although these latest works focus on elegant resolution of the intra-and extracellular conductivities, they seek to determine conductivity on myofiber and "transverse" axes alone, neglecting the effects of the laminar architecture of myocardium. On the cardiac surfaces transverse coupling of myocytes is uniform, however the effects of intramural laminar discontinuities in coupling need to be evaluated with respect to these electrode designs.…”
Section: Analysis Of Bulk Conductivity Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8,33,34 Importantly, although these latest works focus on elegant resolution of the intra-and extracellular conductivities, they seek to determine conductivity on myofiber and "transverse" axes alone, neglecting the effects of the laminar architecture of myocardium. On the cardiac surfaces transverse coupling of myocytes is uniform, however the effects of intramural laminar discontinuities in coupling need to be evaluated with respect to these electrode designs.…”
Section: Analysis Of Bulk Conductivity Estimatesmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Electrical conductivity is thought to be greatest along the myocyte axis allowing most rapid propagation of electrical activation in this direction, and conductivity is commonly assumed to be isotropic transverse to the myocyte axis supporting a slower uniform spread of activation in this plane. [1][2][3][4][5][6][7][8] In this context, knowledge of conductivity in two directions, parallel and transverse to the myofiber axis, is thought sufficient to characterize the electrical action of the heart. This view informs much of the current understanding of cardiac electrophysiology and provides the foundation for interpreting a range of complex phenomena including ventricular fibrillation initiation, maintenance, and termination.…”
mentioning
confidence: 99%
“…More recent extensions of these measuring techniques often involve arrays of electrodes, where the design of the array is based on the four electrode technique [17,2,20,21,22,9,13,12,14,6]. An example of one of these designs is an array of plunge electrodes [9,10,7,3] that demonstrated that porcine ventricular tissue is electrically orthotropic, with three distinct propagation directions.…”
Section: Introductionmentioning
confidence: 99%
“…7 This work has been extended to use two-dimensional models. 22 Possible practical difficulties associated with these systems include the requirement for tiny electrodes and micrometre electrode spacings 2 and the precision required in manufacturing and calibrating these small electrode systems. 23 It has previously been demonstrated, by Hofer et al 6 and Kim et al, 11 that it is possible to use microfabricated arrays to record electrograms in superfused guinea pig and perfused mouse and rabbit papillary muscle preparations.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies suggest that the use of microfabricated arrays with micrometre spacing is technically feasible. 22 In order to recover the cardiac parameters from potential measurements, it is necessary to use a cardiac tissue model. This paper makes use of a previously presented 9 mathematical bidomain model, which is able to include the effects of fibre rotation.…”
Section: Introductionmentioning
confidence: 99%